Pyrethroid resistance and its inheritance in a field population of Hippodamia convergens (Guérin-Méneville) (Coleoptera: Coccinellidae) - Rodrigues, Agna Rita S.; Ruberson, John R.; Torres, Jorge B.; Siqueira, Herbert Álvaro A.; Scott, Jeffrey G. (My University, 2013)
The convergent lady beetle (CLB), Hippodamia convergens (Guérin-Méneville), a species widely distributed and used in biological control, has exhibited high survival under field and laboratory conditions when treated with field rates of the pyrethroid λ-cyhalothrin, a highly unusual phenomenon for a natural enemy. This work investigated and characterized the phenomenon of pyrethroid resistance in a population of this species collected in Georgia, USA. The mechanism and level of resistance were evaluated by treating parental populations with λ-cyhalothrin ± piperonyl butoxide (PBO). The inheritance bioassay utilized parental crosses and backcrosses between parental populations to obtain testable progenies. Adult beetles from populations and progenies were topically treated with different doses of λ-cyhalothrin (technical grade) to calculate knockdown (KD) and lethal (LD) doses, and to investigate the dominance based on a single dose and whether resistance is autosomal and monogenic (null hypothesis). Genetic variation in the parental populations was examined by applying a discriminating dose for resistant individuals (0.5 g/L). The data indicate that resistance is due to at least two factors: knockdown resistance and enzymatic detoxification of the insecticide. The knockdown effect is recessive and linked to the X-chromosome. Variability in proportions of individuals within families dying following knockdown indicated genetic variation in the resistant population. Further studies should be done to investigate the role of sex linked inheritance of resistance in the species and interactions of the various mechanisms involved in resistance.
Citation: Rodrigues, A. R. S., Ruberson, J. R., Torres, J. B., Siqueira, H. A. A., & Scott, J. G. (2013). Pyrethroid resistance and its inheritance in a field population of Hippodamia convergens (Guérin-Méneville) (Coleoptera: Coccinellidae). Retrieved from http://krex.ksu.edu
Keywords: Lady beetles; Pyrethroid; Resistance inheritance; Piperonyl butoxide; λ-cyhalothrin